Pengaruh Karakteristik Biografis Terhadap Kinerja Pengrajin Batik Tulis Home Industry Di Desa Paseseh - Yakut Tatin Hamroh; Iriani Ismail (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
The purposes of this study are to identify the biographical characteristics variables which include age, gender, marital status, number of dependents and tenure that affect the performance of the written batik craftsmen in Paseseh village partially and simultaneously. The hypotheses are (1) to determine whether the age variable has a positive and significant effect on the craftsmen's performance (2) to determine whether the gender variable has a positive and significant effect on the craftsmen's performance (3) to determine whether the marital status variable has a positive and significant effect on the craftsmen's performance (4) to determine whether the variable number of dependents has an effect positive and significant impact on the craftsmen's performance (5) to determine whether the variable of tenure has a positive and significant effect on the craftsmen's performance (6) to determine whether the variables of biographical characteristics (age, gender, marital status, number of dependents, and tenure) have a simultaneous effect on the craftsmen's performance.The results of the F test showed that the biographical characteristics (age, gender, marital status, number of dependents, and tenure) have an effect on the craftsmen's performance with the results of Fcount (26.706) Ftable (3.13) and then R Square is 0.641 (64%).